Surfactant-free microencapsulation of sodium nitrate for high temperature thermal energy storage - Lee, Jaejun; Jo, Byeongnam (Materials Letters, 2020)
Molten salt is typically used as a storage medium in high temperature thermal energy storage (TES) applications. However, salt leakage and the consequent corrosion increase the cost of TES, and hinder the expansion of its application. Therefore, to address these issues, this study proposes a surfactant-free microencapsulation method in which sodium nitrate is enclosed in protective silica (SiO2). The encapsulation ratio of the sodium nitrate core was experimentally measured by comparing the melting peaks of the pure core material and the encapsulated core using differential scanning calorimetry. A high encapsulation ratio (89% on average) was obtained from the sodium nitrate microcapsules synthesized in this study. Additionally, the morphological characteristics of the microcapsules were examined by scanning electron microscopy analysis. Furthermore, Fourier transform infrared spectroscopic analysis confirmed the formation of robust microcapsules without the use of surfactants.
Keywords: Encapsulation ratio; Fourier transform infra reds; High temperature thermal energy storages; ITS applications; Molten salt; Morphological characteristic; Scanning electrons; Surfactant-free; Molten salt; Sol-gel; Surfactant-free encapsulation; Thermal energy storage